The handbook of multilevel theory, measurement, and analysis - Humphrey, Stephen E. (Stephen Earle); LeBreton, James M. (American Psychological Association, 2019)
"The purpose of this handbook is to provide guidance for scholars working in the social and behavioral sciences who wish to consider the implications that multilevel research (i.e., theory, measurement, and analysis) may have for their research programs. The chapters in the book are accessible to researchers from a wide array of research disciplines including (but not limited to) communication, education, sociology, psychology (clinical, developmental, industrial, social), management (strategy, human resources, organizational behavior), and nursing. The book is organized into four parts comprising twenty five chapters. Part I focuses on providing guidance on how to improve theory by integrating a multilevel perspective. Part II transition from focusing largely on issues related to multilevel theory, to a discussion of issues related to multilevel measurement and research design. It is important for those readers who have specified their theory and are now ready to set about collecting data to test it. Part III deals with questions of analysis on multilevel regression analyses, dyadic data analysis, moderated mediation, and network analysis. Part IV consists of two concluding chapters which provide perspective on the development of multilevel research. The first concluding chapter begins by providing a historical perspective on cross-level models, examining the similarities and differences in how the concept of "cross-level models" has been applied by various groups of researchers. It then transitions to the presentation of an integrative cross-level model, discussing its applicability to theory building and testing within the organizational sciences."--Preface. (PsycINFO Database Record (c) 2018 APA, all rights reserved)